Kejawen dalam Pandangan Islam - Imron, Ali; Eryana, Anggi; Suprapto, Rohmat (Institut Agama Islam Negeri Kediri, 2023)
Abstract: The aim of this research is to find out the activities of Javanese culture which is known as kejawen in the village of Demak. People who embrace Islam but do not refuse to preserve the culture of their ancestors. The research methodology used is qualitative by direct observation and interviews with competent informants and documentation. The results of this study were obtained that, starting from the meaning of kejawen in the literal sense, it means Javanese belief. Furthermore, this term refers to everything related to beliefs and customs that develop in Javanese society in particular. From a philosophical point of view, kejawen presents certain teachings whose purpose is to lead people to have good manners, noble values, and an existing divine perspective. With the inclusion of various religious sects in Javanese society over a long period of time, the Kejawen belief experienced acculturation with various other religions. Kejawen Islamic culture is still thick with things that contain shirk, which in Islam itself strictly prohibits this which is explained in the Koran and hadith. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui aktivitas kedudayaan jawa yang disebut dengan istilah kejawen di Desa wilayah Demak. Masyarakat yang memeluk agama islam namun tidak menolak melestarikan kebudayaan para leluhur. Metodologi penelitian yang digunakan adalah kualitatif dengan melakukan observasi secara langsung dan wawancara kepada para narasumber yang berkompeten serta melakukan dokumentasi. Hasil dari penelitian ini diperoleh bahwa, diawali dari makna kejawen dalam arti harfiah bermakna kepercayaan Jawa. Lebih lanjut, istilah ini merujuk pada segala hal yang memiliki hubungan dengan kepercayaan maupun adat-istiadat yang berkembang di masyarakat Jawa khususnya. Dari segi filsafat, kejawen menghadirkan ajaran-ajaran tertentu yang tujuannya menggiring manusia untuk memiliki tata krama, nilai-nilai luhur, serta cara pandang ketuhanan yang berada. Dengan masuknya berbagai aliran keagamaan di masyarakat Jawa dalam rentang periode yang lama, kepercayaan kejawen mengalami akulturasi dengan berbagai agama lain. Kebudayaan islam kejawen masih kental dengan hal-hal mengandung syirik, yang mana di islam sendiri sangat melarang hal tersebut yang mana di jelaskan dalam al’quran dan hadis.